2016
DOI: 10.1186/s40064-016-1712-9
|View full text |Cite
|
Sign up to set email alerts
|

Axillary surgery in women with sentinel node-positive operable breast cancer: a systematic review with meta-analyses

Abstract: Traditionally, women with node-positive operable breast cancer have received complete axillary lymph node dissection (ALND), which is associated with significant morbidity, but recently less invasive alternatives have been explored. We conducted a systematic review of randomised controlled trials assessing alternative approaches to axillary surgery in patients with pathologically-confirmed sentinel node-positive operable breast cancer. We searched on 16/3/15 the Specialized Register of the Cochrane Breast Canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…An SLNB in patients submitted to early-stage breast cancer treatment is a strategy to minimize the risk of morbidities associated with therapy, primarily upper limb lymphedema 3,4,50. Currently, the decrease in practice of ALND after positive SLN for micrometastases or an isolated tumor suggests that ALND is more prognostic than therapeutic 5153.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An SLNB in patients submitted to early-stage breast cancer treatment is a strategy to minimize the risk of morbidities associated with therapy, primarily upper limb lymphedema 3,4,50. Currently, the decrease in practice of ALND after positive SLN for micrometastases or an isolated tumor suggests that ALND is more prognostic than therapeutic 5153.…”
Section: Discussionmentioning
confidence: 99%
“…An SLNB in patients submitted to early-stage breast cancer treatment is a strategy to minimize the risk of morbidities associated with therapy, primarily upper limb lymphedema. 3 , 4 , 50 Currently, the decrease in practice of ALND after positive SLN for micrometastases or an isolated tumor suggests that ALND is more prognostic than therapeutic. 51 53 Although SLNB reduces the risk of developing lymphedema, other factors, including disruption of arm lymphatic vessels 37 , 38 and obesity, 38 , 39 may lead to the onset of this condition, especially when associated with adjuvant radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Schmidt-Hansen et al ont réalisé une méta-analyse des essais comparant un curage axillaire et une radiothérapie de l'aire ganglionnaire axillaire, chez des patientes atteintes d'un cancer du sein opéré avec ganglion sentinelle atteint [19]. Ils ont montré un taux de rechute identique entre les deux cas, mais une morbidité supé-rieure en cas de curage ganglionnaire chirurgical.…”
Section: Lymphoedèmeunclassified
“…When the ACOSOG Z0011 and AMAROS trials were conducted, several breast units stopped performing axillary lymph node dissection (ALND) in patients with one or two affected sentinel lymph nodes (SLN) as these studies proved that ALND was not superior to direct or indirect axillary irradiation . Since these trials were conducted, several systematic reviews and meta‐analyses have supported this data …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Since these trials were conducted, several systematic reviews and meta-analyses have supported this data. 3,4 On the other hand, a recent meta-analysis of randomized trials of ALND versus no ALND showed an improvement in overall survival (OS) and disease-free survival (DFS) in patients who underwent ALND. 5 Importantly, a randomized trial also reported that irradiation of lymph node areas improved DFS and distant DFS.…”
Section: Introductionmentioning
confidence: 99%